The Predictive Value of Left Atrial Strain Following Transcatheter Aortic Valve Implantation on Anatomical and Functional Reverse Remodeling in a Multi-Modality Study - Vattay, Borbála; Nagy, Anikó Ilona; Apor, Astrid; Kolossváry, Márton; Manouras, Aristomenis; Vecsey-Nagy, Milán; Molnár, Levente; Boussoussou, Melinda; Bartykowszki, Andrea; Jermendy, Ádám L.; Kováts, Tímea; Zsarnóczay, Emese; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Transcatheter aortic valve implantation (TAVI) can improve left ventricular (LV) mechanics and survival. Data on the predictive value of left atrial (LA) strain following TAVI are scarce. We aimed to evaluate the association of LA strain measured shortly post-TAVI with functional and anatomical reverse remodeling of the LA and LV, and its association with mortality. Methods We prospectively investigated 90 patients who underwent TAVI. Transthoracic echocardiography including strain analysis was performed shortly after TAVI and repeated 6 months later. CT angiography (CTA) was performed for pre-TAVI planning and 6 months post-TAVI. Speckle tracking echocardiography was used to determine LA peak reservoir strain (LASr) and LV global longitudinal strain (LV-GL), LA volume index (LAVi) was measured by TTE. LV mass index (LVMi) was calculated using CTA images. LA reverse remodeling was based on LASr and LAVi changes, whereas LV reverse remodeling was defined as an improvement in LV-GLS or a reduction of LVMi. The association of severely reduced LASr (<20%) at baseline with changes (Δ) in LASr, LAVi, LV-GLS and LVMi were analyzed using linear regression, and Cox proportional hazard model for mortality. Results Mean LASr and LV-GLS were 17.7 ± 8.4 and −15.3 ± 3.4% at baseline and 20.2 ± 10.2 and −16.6 ± 4.0% at follow-up (p = 0.024 and p < 0.001, respectively). Severely reduced LASr at baseline was associated with more pronounced ΔLASr (β = 5.24, p = 0.025) and LVMi reduction on follow-up (β = 5.78, p = 0.036), however, the majority of the patients had <20% LASr on follow-up (44.4%). Also, ΔLASr was associated with ΔLV-GLS (adjusted β = 2.10, p < 0.001). No significant difference in survival was found between patients with baseline severely reduced LASr (<20%) and higher LASr (≥20%) (p = 0.054). Conclusion LV reverse remodeling based on LVMi was present even in patients with severely reduced LASr following TAVI, although extensive LA damage based on LA strain was demonstrated by its limited improvement over time. Clinical Trial Registration (ClinicalTrials.gov number: NCT02826200).